0
$\begingroup$

Definition of an order of a group: Let $G$ be a group and $a\in G$. Then $a$ is said to have finite order if there exists a $n\ge 1$ such that $a^{n}=e$. If $a$ is of no finite order then $a$ is said to have infinite order.

The question states, let $a$ and $b$ be two elements of a group $G$ such that $a$ has order 3, b has order 2, and $bab^{-1}$=$a^{-1}$.
Prove that $ab$ had order 6 by showing none of $(ab)^{2}$,$(ab)^{3}$,...$(ab)^{5}$ are equal to $e$, but $(ab)^{6}$=$e$. Give an example of a group and elements $a$ and $b$ such that $a$ has order 3, $b$ has order 2, and $bab^{-1}$=$a^{-1}$.

I was only able to do $(ab)^{2}$. Here it is:
$(ab)^{2}$= $abab$
$\qquad$ =$abab^{-1}$
$\qquad$ =$a$ $\,$ $a^{-1}$=$1$

I am stuck trying to do the rest of this problem.

$\endgroup$
  • $\begingroup$ But then,this shows that $ab$ has order $2$,not $6$. $\endgroup$ – астон вілла олоф мэллбэрг Feb 14 '17 at 3:16
  • $\begingroup$ It says I have to show $ab$ has order 6 by showing none of $(ab)^{2}$=$e$. I'm trying figure this out myself $\endgroup$ – behold Feb 14 '17 at 3:20
  • $\begingroup$ Yes, but the question is wrong, as the answer below shows. I know that it may seem unlikely, but that is the case. $\endgroup$ – астон вілла олоф мэллбэрг Feb 14 '17 at 3:23
  • $\begingroup$ Ok. I will notify my professor then $\endgroup$ – behold Feb 14 '17 at 3:24
  • 1
    $\begingroup$ In the symmetric group $S_3$ let $a=(1\ 2\ 3)$ and $b=(1\ 2);$ then $a$ has order $3$ and $b$ has order $2$ and $bab^{-1}=(1\ 3\ 2)=a^{-1}.$ And of course $ab=(1\ 3)$ has order $2;$ there are no elements of order $6$ in $S_3.$ $\endgroup$ – bof Feb 14 '17 at 3:31
4
$\begingroup$

$bab^{-1}=a^{-1}$ implies that $aba=b$.We deduce that $(ab)^2=abab=b^2=e$. The order of $ab$ is 2 and not 6.

$\endgroup$
  • $\begingroup$ it says I have to show $ab$ has order 6 by showing none of $(ab)^{2}$=$e$. I'm trying figure that out myself. I see that your $bab^{-1}$= $a^{-1}$ solution looks about right. The question itself is weird to me $\endgroup$ – behold Feb 14 '17 at 3:23
  • $\begingroup$ It's also kind of weird that the assumption that $a$ has order $3$ is not needed in showing $(ab)^2=e,$ and that the notation $b^{-1}$ is used when $b$ is of order $2.$ $\endgroup$ – bof Feb 14 '17 at 3:37
  • $\begingroup$ exactly. I might just take the whatever I can get on the problem $\endgroup$ – behold Feb 14 '17 at 3:40
1
$\begingroup$

I'm going to outline what I think the problem should be, and solve that.

Let us suppose instead that $a^2=e$, $b^3=e$, along with $bab^{-1} = a^{-1} = a$. The latter is equivalent to $ab=ba$. Then $$\begin{align} (ab)^2 &= abab = baab = b^2 = b^{-1} \neq e \\ (ab)^3 &= (ab)b^{-1} = a \neq e \\ (ab)^4 &= ((ab)^2)^2 = b^4 = b \neq e \\ (ab)^5 &= abb = ab^2 = ab^{-1} \neq e \\ (ab)^6 &= ((ab)^3)^2 = a^2 = e \end{align} $$

Essentially, what happens here is that, because $a$ commutes with $b$, $(ab)^n = a^n b^n$, and you need $2\mid n$ for $a^n=e$ and $3 \mid n$ for $b^n=e$.

$\endgroup$
  • $\begingroup$ Okay. When I did $(ab)^{2}$ I got 1. For some reason you did your much different. This looks about right $\endgroup$ – behold Feb 14 '17 at 3:47
  • $\begingroup$ @Chappers, You mixed up $a$ and $b$! It is $a$ that has order $3$ and $b$ has order $2$. $\endgroup$ – Nicky Hekster Feb 14 '17 at 6:22
  • $\begingroup$ @NickyHekster As others have noted and I say in the first two sentences, the problem as posed is wrong. This is what I think the question wanted to ask: if one instead has the orders of $a$ and $b$ the other way round, $ab$ really does have order $6$. $\endgroup$ – Chappers Feb 14 '17 at 13:29

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.